Depictions of feminism in Barbie film teasers and trailers - Fajri, Karunia Octaviani; Anjaniputra, Agung Ginanjar (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2024)
The present study scrutinises the depictions of feminism in Barbie’s teasers and trailers, which breaks through the perspective of three meta-functions which are representation, interaction, and composition. The grammar of visual design (GVD) of Kress and Van Leeuwen (2021) is employed as the theoretical framework of the study. Secondary data are drawn on the YouTube channel of Warner Bros. Pictures for being applied to inclusion and exclusion criteria to qualify for the feminism features. A total of 43 frames from 7 selected videos are gathered to reveal that feminism is depicted in teasers and trailers of Barbie. Through narrative representation possessed by all the collected frames, women’s empowerment followed by the physique of beauty are the dominant features of feminism in teasers and trailers of Barbie 2023. The three meta-functions that are employed to explore how Barbie teasers and trailers convey the tropes of feminism are discussed. Through discourse intermediation (Fowler & Mountz, 2024), which in this context is the discourse of feminism, the current study constitutes a miniscule endeavor to equip educators and academics by applying language skills and attitudes to facilitate inclusive opportunities.